Temporal trends in paediatric bacterial meningitis in a tropical Australian region: 1992–2014. (13th May 2018) - White, Stephanie; Katf, Hala; Baird, Rob; Francis, Joshua
Abstract : Aim: The epidemiology of community‐acquired bacterial meningitis has changed following the introduction of routine immunisation against common causative organisms. Indigenous children living in the Northern Territory, Australia, have high rates of bacterial infections. This study describes changes in the epidemiology of childhood bacterial meningitis and the distribution of the burden of disease in the Top End. Methods: A retrospective review of cases derived from hospital medical records and laboratory data was performed. Inclusion criteria were children aged 3 months to 14 years of age, admitted to Royal Darwin Hospital between 1992 and 2014 and diagnosed with bacterial meningitis. Annual incidence of bacterial meningitis and the distribution of causative pathogens are described. Demographic data, investigations, treatment and outcomes were compared between Indigenous and non‐Indigenous children. Results: There were 137 cases of childhood bacterial meningitis identified over the 23‐year period. The incidence reduced from 21 per 100 000 children per year for 1992–2002 to 11 per 100 000 per year for 2003–2014 ( P = 0.0025). Haemophilus influenzae type b, Streptococcus pneumoniae and Neisseria meningitidis were the most common causative organisms, with a reduction in cases for each pathogen observed across the study period. Indigenous children were over‐represented (104/137, 76%). Case fatality rate was 8% (11/137); 91% of fatal cases presented to a remote facility. Conclusions: The incidence of childhood bacterial meningitis has declined in the Northern Territory of Australia, but Indigenous children are disproportionately affected. Routine immunisation is beneficial for all, although further efforts to 'Close the Gap' between health outcomes in Indigenous and non‐Indigenous Australians is required.